Human Umbilical Cord Perivascular Cells Exhibited Enhanced Migration Capacity towards Hepatocellular Carcinoma in Comparison with Bone Marrow Mesenchymal Stromal Cells: A Role for Autocrine Motility Factor Receptor. (23rd July 2014) - Bayo, Juan; Fiore, Esteban; Aquino, Jorge B.; Malvicini, Mariana; Rizzo, Manglio; Peixoto, Estanislao; Alaniz, Laura; Piccioni, Flavia; Bolontrade, Marcela; Podhajcer, Osvaldo; Garcia, Mariana G.; Mazzolini, Guillermo
Abstract : Hepatocellular carcinoma (HCC) is the third cause of cancer-related death worldwide. Unfortunately, the incidence and mortality associated with HCC are increasing. Therefore, new therapeutic strategies are urgently needed and the use of mesenchymal stromal cells (MSCs) as carrier of therapeutic genes is emerging as a promising option. Different sources of MSCs are being studied for cell therapy and bone marrow-derived cells are the most extensively explored; however, birth associated-tissues represent a very promising source. The aim of this work was to compare the in vitro and in vivo migration capacity between bone marrow MSCs (BM-MSCs) and human umbilical cord perivascular cells (HUCPVCs) towards HCC. We observed that HUCPVCs presented higher in vitro and in vivo migration towards factors released by HCC. The expression of autocrine motility factor (AMF) receptor, genes related with the availability of the receptor on the cell surface (caveolin-1 and -2) and metalloproteinase 3, induced by the receptor activation and important for cell migration, was increased in HUCPVCs. The chemotactic response towards recombinant AMF was increased in HUCPVCs compared to BM-MSCs, and its inhibition in the conditioned medium from HCC induced higher decrease in HUCPVC migration than in BM-MSC. Our results indicate that HUCPVCs could be a useful cellular source to deliver therapeutic genes to HCC.